--- a/Nominal/Ex/Height.thy Tue Jan 18 21:28:07 2011 +0100
+++ b/Nominal/Ex/Height.thy Wed Jan 19 07:06:47 2011 +0100
@@ -1,5 +1,5 @@
theory Height
- imports "../Nominal2"
+ imports "Lambda"
begin
text {*
@@ -7,96 +7,29 @@
the height of a lambda-terms behaves under substitution.
*}
-atom_decl name
-
-nominal_datatype lam =
- Var "name"
- | App "lam" "lam"
- | Lam x::"name" l::"lam" bind x in l ("Lam [_]._" [100,100] 100)
-
-
-text {* Definition of the height-function on lambda-terms. *}
-
-function
- height :: "lam \<Rightarrow> int"
-where
- "height (Var x) = 1"
-| "height (App t1 t2) = (max (height t1) (height t2)) + 1"
-| "height (Lam [a].t) = (height t) + 1"
- apply(rule_tac y="x" in lam.exhaust)
- apply(simp_all)[3]
- apply(simp add: lam.eq_iff)
- apply(simp add: lam.distinct)
- apply(simp add: lam.distinct)
- apply(simp add: lam.eq_iff)
- apply(simp add: lam.distinct)
- apply(simp add: lam.eq_iff)
- sorry
-
-termination
- apply(relation "measure size")
- apply(simp_all add: lam.size)
- done
-
-text {* Definition of capture-avoiding substitution. *}
-
-function
- subst :: "lam \<Rightarrow> name \<Rightarrow> lam \<Rightarrow> lam" ("_[_::=_]" [100,100,100] 100)
-where
- "(Var x)[y::=t'] = (if x=y then t' else (Var x))"
-| "(App t1 t2)[y::=t'] = App (t1[y::=t']) (t2[y::=t'])"
-| "\<lbrakk>atom x \<sharp> y; atom x \<sharp> t'\<rbrakk> \<Longrightarrow> (Lam [x].t)[y::=t'] = Lam [x].(t[y::=t'])"
-apply(case_tac x)
-apply(simp)
-apply(rule_tac y="a" and c="(b, c)" in lam.strong_exhaust)
-apply(simp_all)[3]
-apply(blast)
-apply(blast)
-apply(simp add: fresh_star_def fresh_Pair)
-apply(blast)
-apply(simp add: lam.eq_iff)
-apply(simp add: lam.distinct)
-apply(simp add: lam.distinct)
-apply(simp add: lam.eq_iff)
-apply(simp add: lam.distinct)
-apply(simp add: lam.eq_iff)
-sorry
-
-termination
- apply(relation "measure (size o fst)")
- apply(simp_all add: lam.size)
- done
-
-text{* The next lemma is needed in the Var-case of the theorem below. *}
lemma height_ge_one:
shows "1 \<le> (height e)"
-apply(nominal_induct e rule: lam.strong_induct)
-apply(simp_all)
-done
-
-text {*
- Unlike the proplem suggested by Wang, however, the
- theorem is here formulated entirely by using functions.
-*}
+by (induct e rule: lam.induct)
+ (simp_all)
theorem height_subst:
- shows "height (e[x::=e']) \<le> ((height e) - 1) + (height e')"
+ shows "height (e[x::=e']) \<le> height e - 1 + height e'"
proof (nominal_induct e avoiding: x e' rule: lam.strong_induct)
case (Var y)
- have "1 \<le> height e'" by (rule height_ge_one)
+ have "1 \<le> height e'" using height_ge_one by simp
then show "height (Var y[x::=e']) \<le> height (Var y) - 1 + height e'" by simp
next
case (Lam y e1)
- have ih: "height (e1[x::=e']) \<le> ((height e1) - 1) + (height e')" by fact
+ have ih: "height (e1[x::=e']) \<le> height e1 - 1 + height e'" by fact
moreover
have vc: "atom y \<sharp> x" "atom y \<sharp> e'" by fact+ (* usual variable convention *)
- ultimately show "height ((Lam [y].e1)[x::=e']) \<le> height (Lam [y].e1) - 1 + height e'" by simp
+ ultimately show "height ((Lam y e1)[x::=e']) \<le> height (Lam y e1) - 1 + height e'" by simp
next
case (App e1 e2)
- have ih1: "height (e1[x::=e']) \<le> ((height e1) - 1) + (height e')"
- and ih2: "height (e2[x::=e']) \<le> ((height e2) - 1) + (height e')" by fact+
- then show "height ((App e1 e2)[x::=e']) \<le> height (App e1 e2) - 1 + height e'" by simp
+ have ih1: "height (e1[x::=e']) \<le> (height e1) - 1 + height e'"
+ and ih2: "height (e2[x::=e']) \<le> (height e2) - 1 + height e'" by fact+
+ then show "height ((App e1 e2)[x::=e']) \<le> height (App e1 e2) - 1 + height e'" by simp
qed
end